Recrutement de prestataires de services maîtrisant le français : conseils et stratégies - Institut du savoir sur la santé mentale et les dépendances chez les enfants et les jeunes (2023)

La première étape de la validation transculturelle des versions anglophones des tests de l'horloge et du Mini-Mental pour mesurer les capacités cognitives des Franco-Ontariens âgés de plus de 65 ans - Larocque, Sylvie; Lavoie, Anne-Marise; Omri, Nadia (Reflets, 2021)
La maladie d’Alzheimer est un syndrome neurodégénératif chronique caractérisé par un déclin cognitif et mnésique. Les personnes atteintes par cette maladie développent des affections rattachées à la langue. Il est important de faire passer des tests de dépistage dans la langue maternelle de la personne puisque l’aptitude linguistique décline avec la progression de la maladie. De manière générale, le Mini-mental et le test de l’horloge sont administrés en anglais aux francophones du nord de l’Ontario ce qui peut mener à une sous-évaluation de leurs capacités cognitives et à un diagnostic erroné. Voilà pourquoi le but de cette recherche était de développer et valider les tests psychométriques francophones administrés aux Franco-Ontariens. Le Mini-mental et le test de l’horloge ont été traduits selon la validation transculturelle de Caron (1999) et testés auprès des francophones du Grand Sudbury qui souffraient de déficits cognitifs (N=14). Aucune différence statistique (p>.05) entre les scores de la traduction franco-ontarienne du test de l’horloge et du Mini-mental comparés aux tests originaux n’a été détectée. Bien que d’autres recherches soient nécessaires, selon les auteures, ces traductions permettront d’assurer un dépistage juste de cette maladie chez les francophones âgés en situation minoritaire. Mots-clés : dépistage d’Alzheimer, Mini-mental de Folstein, test de l’horloge, traduction transculturelle

Reach, adoption, and implementation strategies of a telehealth falls prevention program: perspectives from francophone communities across Canada. - O’Neil, Jennifer; Dionne, Nathalie; Marchand, Sylvie; Cardinal, Dominique; Handrigan, Grant; Savard, Jacinthe (Health Promotion and Practice, 2024)
Introduction. A fall may impact a person’s physical, emotional, and psychological well-being. Fall prevention programs are being implemented to reduce these negative outcomes. However, linguistic barriers in health services may reduce access to such prevention programs. A telehealth fall prevention program was designed to increase access to such programs in French for Francophone minority communities in Canada. This capacity-building project aimed to support community partners to deliver this telehealth program and document strategies used to reach, adopt, and implement the program within various Francophone and Acadian Minority Communities. Methods. A sequential explanatory mixed methodology was used to document reach, adoption, and implementation strategies and describe the lived experiences of program facilitators and organization representatives. Reach, adoption, and implementation were documented and analyzed descriptively, while lived experiences were analyzed using content analysis following the Consortium Framework for Implementation Research. Results. Twelve organization representatives or program facilitators from eight organizations operating in four different provinces participated in the study. Three themes emerged from the qualitative data on reach and adoption: external context, internal context, and capacity building. Four themes were identified as barriers and facilitators to implementation: level of preparation and time management, interpersonal relations and telepresence, exercise facilitation and safety, and technological problem-solving. Conclusion. Using tailored reach and adoption strategies such as prioritizing provinces with higher proportions of needs and training local community program facilitators may lead to the successful implementation of a new telehealth fall prevention program. Results from this study could potentially inform other primary prevention programs or telehealth program implementation.

Problèmes d’accès aux services en français ? Contactez-nous. Nous pouvons vous aider [infographie] - Ombudsman de l'Ontario (2022)

Problems accessing services in French? Contact us. We can help [infographie] - Ontario Ombudsman (2022)

Je suis insatisfait(e) des services de santé reçus. Que faire ? Comment procéder ? [infographie] - Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada; Société Santé en français (2022)

Boîte à outils virtuelle de soins culturellement adaptés pour les francophones dans les foyers de SLD - Réseau du mieux-être francophone du Nord de l’Ontario (2022)

Processus de développement d’une trousse d’accompagnement pour l’examen médical des nouveaux arrivants francophones : un exemple de coopération - Sanou, Boroma; Beaudoin, Monique; Gauthier, Alain P.; Chomienne, Marie-Hélène; Prud’homme, Denis; Kpazaï, Georges (Revue de la Diversité de la Recherche en Santé, 2020)
While over the half of Francophone immigrants living in Ontario come from Africa and the Caribbean, Canadian-trained health professionals are not sufficiently familiar with the health problems that newcomers may face. With this in mind, in a multi-disciplinary partnership, the Center for Rural and Northern Health Research, the Centre de santé communautaire du grand Sudbury, l’Institut du savoir Montfort, the School of Human Kinetics at Laurentian University, and a group of French-speaking immigrants from the City of Greater Sudbury, developed using a collaborative research approach, a newcomer’s medical examination toolkit for health professionals and social services. The toolkit development process involved several steps: 1) establishing a partnership between the above-mentioned organizations; 2) literature review to identify the most common health problems; 3) selection of the most common problems that are not necessarily those that health professionals encounter in everyday practice; 4) writing of draft versions with emphasis on some important aspects of the disease; 5) validation of the fact sheets by the partners; 6) the restitution of the final fact sheets (25 fact sheets including 3 on the general examination, 10 related to certain tropical diseases, 8 sheets related to the signs and symptoms most frequently encountered by health professionals and the other 4 on health care in Ontario); and 7) the development of a digital infograph to ensure greater visibility of the Toolkit for the medical examination of Francophone newcomers.